Recent progress in high resolution X-ray customised detection systems. Issue 1 (1st December 2022) - Vacchi, A; Cirrincione, D; Altissimo, M; Antonelli, M; Aquilanti, G; Bellutti, P; Bertuccio, G; Borghi, G; Carlomagno, I; Cautero, G; Ficorella, F; Gandola, M; et al.
Abstract: The results of a collaborative development activity aimed to the realization of multi-cell detectors based on monolithic SDD pixel technology will be described. Two kind of detection systems, skilled for the light lines at synchrotrons, have been brought to high levels of finalization and integration; a 64 cells detection system dedicated to absorption spectroscopy (XAFS) and a 32 cells detector for the X-ray microscopy (TwinMic). The main targets of this effort, led in a tight collaboration with the beam lines scientists, were large sensitive area, high rate capabilities, state of the art efficiency and energy resolution. The aim is to reduce the beam time demand for each single measurement while delivering a cutting edge analytical power. All basic elements of those detection systems, from the detector's design and production to the front-end and read-out electronics including the final engineering of the integrated system were customized to the specific use addressed.